Project Respirators: art and education in performance in the Anthropocene (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
The article presents the Respiradores Project as an artistic-pedagogical practice aimed at lower secondary school students. It is justified by the need to propose practices that integrate art, education, and sustainability in response to the ethical and environmental challenges that characterize the Anthropocene. The methodology adopts a qualitative approach, designed as a case study, grounded in audiovisual records and observations conducted by the teacher-artist. The theoretical framework brings together ecosophy and performance studies. The study concludes that the experience fostered the development of critical sensitivity, ecological awareness, and collective engagement.
Keywords: respiradores project; ecosophy; performance studies; anthropocene